Analysis of the Islamic Religious Education Curriculum and the Function of Achieving Character Education Goals - Ainul Jaria Maidin; Salma Begum; Maryam Rashid Saleh Al Tamimi; Muneera Mohammed Al Dossary; Abdallah El-Khatib (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
This study analyzes the Islamic Religious Education (PAI) curriculum in relation to the achievement of character education goals in Indonesia. Character education is an integral part of the national education system aimed at developing students' moral and ethical values. The PAI curriculum plays a crucial role in achieving this goal through the teaching of religious values integrated into various aspects of learning. The research methods used include literature review and analysis of the applicable PAI curriculum documents. The results show that the PAI curriculum is designed to develop students' character through materials covering aspects of faith, worship, and morality. However, there are challenges in its implementation, such as the lack of teacher training, limited resources, and the mismatch between theory and practice in the field. To address these challenges, it is recommended to enhance teacher competencies through continuous training, provide adequate educational resources, and conduct ongoing curriculum evaluations. Thus, the PAI curriculum can be more effective in supporting the formation of students' integrity, ethics, and strong personalities in accordance with national education goals